Uso de jasmonatos na fitorremediação e tolerância a cádmio: uma revisão sistemática - Souza, Raja Yamma Rodrigues (Universidade Federal de São Carlos, 2023)
The emission of cadmium (Cd) into the environment due to industrial, agricultural, and urbanization activities poses risks to agricultural production areas and, consequently, to human health. Among the promising decontamination strategies, phytoremediation is reported to be a low-cost and environmentally friendly solution. In this sense, different species have been studied to understand which plants are more tolerant of contaminated environments and suitable for Cd phytoremediation. However, the effects of applying phytoregulators on modulating plant metabolism under conditions of Cd stress have yet to be elucidated. Therefore, this study aimed to investigate phytoremediation and plant tolerance under exogenous jasmonate (JA) application in different plants grown in a Cd-contaminated environment. We used the systematic review methodology by defining the scope, planning, identifying, and searching, screening the articles, assessing eligibility, and interpreting and presenting the results. The eligible publications indicate that the application of JA to plants grown in a contaminated environment decreases Cd accumulation and malondialdehyde (MDA) content while increasing antioxidant activity (superoxide dismutase, SOD, catalase, CAT, peroxidase, POD, and ascorbate peroxidase, APX). Thus, we conclude that applying JA decreases phytoremediation and increases the tolerance of plants grown in a Cd environment. The results of this review were written up as a review article and submitted to the scientific journal Environmental Chemistry Letters.
Role of jasmonates in cadmium phytoremediation and plant tolerance: a systematic review
Keywords: metal pesado; estresse oxidativo; peroxidação lipídica; antioxidantes; toxicidade; resposta de defesa; Heavy metal; Oxidative stress; Lipid peroxidation; Antioxidants; Cadmium toxocity; Defese response; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL::NUTRICAO E CRESCIMENTO VEGETAL